Magnetoelectric memory cell based on 0.5Ba(Zr0.2Ti0.8)O3-0.5Ba0.7Ca0·3TiO3/Fe65Co35 thin films. (April 2023) - Yin, Xin; Han, Yemei; Ma, Meibing; Shen, Kaisong; Hu, Kai; Sun, Zheng; Wang, Fang; Wu, Haitao; Zhang, Kailiang
Abstract: In this study, 0.5Ba(Zr0·2 Ti0.8 )O3 -0.5Ba0·7 Ca0·3 TiO3 (0.5BZT-0.5BCT) thin films were deposited on Pt/Ti/SiO2 /Si substrate, and then small area Fe65 Co35 (FeCo) films were deposited on 0.5BZT-0.5BCT films. The hysteresis loops and piezoelectric curves of 0.5BZT-0.5BCT films were studied. The results show that the piezoelectric displacement of 0.5BZT-0.5BCT films is 63 Å, the residual polarization intensity is 2.76 μC/cm 2 and the coercive field is 110 kV/cm. 0.5BZT-0.5BCT/FeCo composite films exhibit typical magnetic hysteresis loops and stripe-like domains, the in-plane and out-of-plane coercivities are 10 Oe and 94 Oe, respectively, which indicates that the thin films have good soft magnetic properties. The current-voltage (I–V) curves of FeCo films on 0.5BZT-0.5BCT films were studied, the I–V behaviors of the thin films could be modulated by applying bias voltage, resulting in a resistance switching behavior. The maximum resistance change is 94% at 10 V bias voltage and 1 V scan voltage. Highlights: 0.5Ba(Zr0.2 Ti0.8 )O3 -0.5Ba0.7 Ca0.3 TiO3 /Fe65 Co35 thin films are fabricated. Multiferroicity and bias voltage modulated resistance switching behavior are studied. A maximum resistance change of 94% is obtained by using 50 μm × 500 μm Fe65 Co35 films.